Modal Characteristics of Two Operating Power Transmission Poles - Shen-En Chen; Kaoshan Dai (Shock and Vibration)
Unique conductor-pole couplings complicate the dynamic behaviors of electric transmission pole line systems. Finite element modeling is performed on two typical transmission poles used in southeastern USA – a steel pole and a prestressed concrete pole. The two poles are representative of unique structure types: a heavy rod-like structure and a lightweight, shell-type structure. Since coupling issues between the pole and the cable introduce great complexities for modeling the pole line system, simplified numerical models are used. Limited full-scale modal test results are presented to verify the numerical models. The prestressed concrete pole is shown to be easier for mode identification than the steel pole – but both numerical models show complicated coupled vibration modes. This study is part of a larger study to establish an understanding of the dynamic response analyses of power grid under ground vibrations.